FREE CURRICULUM MANAGEMENT BASED ON CONSTRUCTIVIST THEORY - Makalao, Dwi Ajeng Maulidya; Asy’ari, Asy’ari; Supardi, Acep; Badrudin, Badrudin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to describe the Free Curriculum based on Constructivism Theory at SMK Negeri 1 Rancaekek. The research employs a qualitative approach with data collection methods through interviews and observations. The results indicate that in curriculum planning, teachers formulate learning outcomes based on student needs in accordance with constructivist principles. The implementation of the free curriculum is carried out by applying a student-centered approach and involving interaction with the environment. Teachers also act as facilitators who support students' knowledge construction. Learning evaluation includes self-reflection and a review of materials to assess students' understanding. The main challenge is the lack of facilities and infrastructure, which is addressed by optimizing resource utilization. In conclusion, the application of constructivism theory in the Free Curriculum at SMK Negeri 1 Rancaekek has successfully created adaptive and student-centered learning.